Apparent factor IX inhibitor. - Jameela, S; Rozika, P; Rizalman, J; Phan, CL; Visalachy, P; Chang, KM (Penerbit UKM, 2011)
The causes of an isolated prolonged activated partial thromboplastin time (APTT) with a normal prothrombin time (PT) are either a deficiency of clotting factors VIII, IX, XI or XII or the presence of an inhibitor. The inhibitor may be specific to an individual clotting factor or it may be a non-specific inhibitor like the lupus anticoagulant which has opposite therapeutic implications. We report a patient referred to our hospital for treatment that was previously diagnosed at another medical institution as an acquired factor IX inhibitor following an investigation for a prolonged APTT. On further testing this turned out to be a potent lupus anticoagulant which interfered with the phospholipid-dependent factor assays. The use of dilution studies, chromogenic assays and phospholipid neutralization can help differentiate these inhibitors. Great care must be taken in the interpretation of factor assays in the presence of lupus anti-coagulant to avoid misdiagnosis and inappropriate treatment.